INTENSIF CLASS SEBAGAI BENTUK PEMBELAJARAN ONLINE GITAR KLASIK DI K2C MUSIC EDUCITY SURABAYA - Rifky, Roby Stevani (Jurnal Pendidikan Sendratasik, 2024)
In conditions that require the teaching and learning process to be carried out online via internet media, it provides a new teaching style for educators to convey material to their students. K2C Music Educity Surabaya made a program, namely intensive classes as online classical guitar learning to maximize student learning in the Covid-19 pandemic era. This article aims to describe an intensive class program as online classical guitar learning which is held at K2C Music Educity Surabaya. The approach used in this research is descriptive qualitative. Data collection was carried out by observation, photography and interviews. Data analysis was carried out through the data reduction stage, testing the validity of the data through triangulation, and drawing conclusions. The results showed that the classical guitar class intensive learning program at K2C Music Educity Surabaya applied an online learning method (Web Course) in the form of two-way communication. The K2C Music Educity Surabaya learning model can facilitate student teaching and learning because teachers can evaluate student learning processes directly. There are two kinds of intense class programs on classical guitar, namely 8 meetings in one month and 12 meetings in one month. With intense classes, students can complete song material more quickly because more practice is monitored directly by the teacher, and this intense class shortens the duration of learning because there is more than one meeting in one week.